Industry 4.0: key findings and analysis from the literature arena. Issue 8 (30th July 2019) - G., Rejikumar; Sreedharan V., Raja; P., Arunprasad; Persis, Jinil; K.M., Sreeraj
Abstract : Purpose: In recent years, a new transformation known as Industry 4.0 has drawn much attention throughout the world, and numerous investigations have fundamentally looked into the uprising concept. However, few have concentrated on the literature review. Taking this as motivation, the authors endeavored to assess the different attributes of Industry 4.0. The paper aims to discuss these issues. Design/methodology/approach: This review concentrated on linking the articles from different database and distinguishing the attributes of Industry 4.0. The authors assessed 85 articles from scholarly database and peer-reviewed journals on Industry 4.0 through the selection of the Mayring (2004) procedure. The examination included a four-advance process, in particular, material gathering, engaging investigation, classification of the choice and material assessment. Findings: The study backs experts and readers to comprehend the spread of Industry 4.0 in various ventures. For academicians, this gives an extensive rundown of Industry 4.0 attributes. Besides, the writing review gives a chance to comprehend the idea of Industry 4.0 in detail. Further, the outcome aggregates the success factor, failure factor, business model, potential and difficulties in the context of Industry 4.0. Research limitations/implications: Many areas such as supply chain, circular economy and healthcare have started exploring Industry 4.0. However, few specific cases have reported about it, and no generic model is found for real-time application. Practical implications: The study serves as reference material for researchers and practitioners to understand the spread of Industry 4.0 and utilize the concept of Industry 4.0 for real-life application. Originality/value: The study focuses on reporting the potential, challenges, business model and pre-requites of Industry 4.0.